P68 Lean - Looking with fresh eyes. (1st October 2013) - Bridger, Susan; Collins, Debbie; Loan, Rebecca; Tomsett, Jacqui
Abstract : Introduction: The hospice has continually strived to provide the most efficient and streamlined services possible, right across the organisation. In August 2011 in was decided to introduce 'Lean'.organisational improvement principles. 4 staff from different departments were trained as Lean Advisers to embed the principles of Lean within all areas of the hospice. This is the journey of the introduction and development of 'Lean' to support organisational improvement. Aim: To demonstrate the development of the role of the 'LEAN' Advisers to empower and support staff in their review of departmental processes using 'LEAN' principles and techniques. To discuss process and outcomes of projects undertaken in clinical care, fundraising, staff support and environmental efficiency To discuss lessons learnt To discuss where we go from here Methods: Developed a timeline to plot the journey to introduce Lean Principles. Ongoing training provided on a voluntary basis by a Lean consultant Use of a variety of Lean tools to collect and analyse data Results: To date two projects have been completed - 1 reviewing and streamlining of the patients journey through the hospice which has resulted in cost savings on staffing and an increase in patient contacts by community staff. 2 the running and management of OT & Physio equipment stores which has resulted in a more efficient and safer service to patients. 3 other projects are in progress. Conclusion: It is far too easy to offer solutions to a problem before understanding what is really going on It is far too easy to implement a process/solution for a problem and then think the job is done A group of people from different backgrounds with LEAN training can make a massive difference to a service